Housing Right in the Constitution (Comparative Legal Analysis) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
in this scientific article by the researcher, The construction of thousands of residential buildings over the past five years serves as clear evidence of this. In conclusion, it should be noted that the consistent implementation of the constitutional foundations of housing reforms serves as a guarantee for the realization and provision of citizens' housing rights.